Hubungan Self Care dengan Kadar Glukosa Darah pada Pasien Diabetes Mellitus di Puskesmas Kedungwuni 1 - Nico Octario Sotya Negara; Dyah Wiji Puspita Sari; Muh.Abdurrouf (STIKes Ibnu Sina Ajibarang, 2025)
Background: Diabetes mellitus (DM) is a chronic disease and a global health problem with an increasing prevalence that often leads to serious complications if not well controlled. Optimal self-care behavior, including diet regulation, physical activity, blood glucose monitoring, and adherence to medication, plays a crucial role in maintaining stable blood glucose levels and improving quality of life. Objective: This study aims to investigate the relationship between self-care behavior and blood glucose levels among individuals diagnosed with diabetes mellitus who are receiving treatment at Kedungwuni 1 Public Health Center. Methods: This research employed an observational analytical design with a cross-sectional approach. A total of 109 respondents diagnosed with DM were selected through total sampling. Data on self-care behavior were collected using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire, while blood glucose levels were measured using a glucometer. Data were analyzed using the Spearman correlation test with a significance level of α = 0.05. Results: The findings showed that most respondents demonstrated poor self-care behavior (72.5%) and almost half were within the diabetes range of blood glucose levels (49.5%). Bivariate analysis revealed a significant positive correlation between self-care behavior and blood glucose levels (p = 0.000; r = 0.547). Conclusion: Better self-care behavior is associated with better blood glucose control. These results emphasize the importance of strengthening health education and self-management programs to improve self-care practices in diabetic patients.